The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/es010182c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pb(II) and Eu(III) by Oxide Minerals in the Presence of Natural and Synthetic Hydroxamate Siderophores

Abstract: Trihydroxamate siderophores have been proposed for use as mediators of actinide and heavy metal mobility in contaminated subsurface zones. These microbially produced ligands, common in terrestrial and marine environments, recently have been derivatized synthetically to enhance their affinity for transuranic metal cations. However, the interactions between these synthetic derivative and adsorbed trace metals have not been characterized. In this paper we compare a natural siderophore, desferrioxamine-B (DFO-B), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 46 publications
1
39
0
4
Order By: Relevance
“…Adsorption of the metallophore is considered a prerequisite in the process of ligand-controlled dissolution (Stumm 1997), and several studies have shown metallophore-promoted dissolution rates to be proportional to the concentration of the ligand adsorbed on the mineral surface (Cheah et al 2003;Duckworth et al 2014;Duckworth and Sposito 2005a;Reichard et al 2005). However, adsorption retains metallophores and metal-metallophore complexes at the surfaces of environmental reactive compounds, thereby reducing the diffusive flux of the target metal toward the organism (Duckworth et al 2008;Haack et al 2008;Kraemer et al 2002;Siebner-Freibach et al 2004. The extent to which metallophores are retained depends on how strongly the ligands and complexes interact with environmental reactive compounds and on the abundance of reactive surfaces.…”
Section: Metallophores and The Geochemistry Of Metal Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption of the metallophore is considered a prerequisite in the process of ligand-controlled dissolution (Stumm 1997), and several studies have shown metallophore-promoted dissolution rates to be proportional to the concentration of the ligand adsorbed on the mineral surface (Cheah et al 2003;Duckworth et al 2014;Duckworth and Sposito 2005a;Reichard et al 2005). However, adsorption retains metallophores and metal-metallophore complexes at the surfaces of environmental reactive compounds, thereby reducing the diffusive flux of the target metal toward the organism (Duckworth et al 2008;Haack et al 2008;Kraemer et al 2002;Siebner-Freibach et al 2004. The extent to which metallophores are retained depends on how strongly the ligands and complexes interact with environmental reactive compounds and on the abundance of reactive surfaces.…”
Section: Metallophores and The Geochemistry Of Metal Bioavailabilitymentioning
confidence: 99%
“…Thus, metallophores may affect the fate and transport of metals that are not necessarily the target of biological uptake. Metallophores have been shown to bind (Anderegg et al 1963;Batka and Farkas 2006;Boukhalfa et al 2007;Christenson and Schijf 2011;Dahlheimer et al 2007;Farkas et al 2008;Frazier et al 2005;Hakemian et al 2005;Hernlem et al 1996Hernlem et al , 1999Jarvis and Hancock 1991;Mishra et al 2009;Moll et al 2008a, b, c;Whisenhunt et al 1996) and solubilize (Biver and Shotyk 2012;Brainard et al 1992;Cornejo-Garrido et al 2008;Dahlheimer et al 2007;Frazier et al 2005;Hakemian et al 2005;Hepinstall et al 2005;Kraemer et al 1999Kraemer et al , 2002Manecki and Maurice 2008;Mishra et al 2010;Schenkeveld et al 2014b; Wolff-Boenisch and Traina 2007b) a number of metals (e.g., Al, Am, Bi, Cm, In, Ru, Pb, Pd, Pt, Pu, Sb, Th, U, and a number of rare earth elements) which are not currently thought to have significant intracellular metabolic roles in most organisms and may even be toxic. These observations have led to the assertion that metallophores may affect the rate of dissolution and transport of these toxic metals in the environment, as well as to the suggestion that metallophores may have utility as remediative agents in environmental systems contaminated with toxic metals.…”
Section: Metallophores and Contaminant Metals: Mobilization Uptake mentioning
confidence: 99%
“…(Table 1). The maximum surface excess (n max ) for DFOB on manganite [n max = 32 ± 5 mmol kg -1 at pH = 8 (Duckworth and Sposito 2005b)] is significantly higher than on goethite [n max = 1.23 ± 0.18 mmol kg -1 at pH = 5 (Cheah et al 2003)], although sorption of DFOB on goethite may increase at higher pH (Kraemer et al 2002). Given that dissolution rates at corresponding conditions differ by [100-fold (Duckworth and Sposito 2005b), increased surface excess does not adequately explain the rapid dissolution rates of a-MnOOH relative to a-FeOOH.…”
Section: Siderophore-promoted Dissolution Of Mn and Fe Mineralsmentioning
confidence: 99%
“…In recent years, adsorption has been shown to be an effective and economically feasible alternative method for removal of heavy-metal ions. [6][7][8] Nonspecific sorbents such as activated carbon, [9,10] metal oxides, [11,12] silica, [13][14][15] ion-exchange resins, and biosorbents [16] have been used. Specific sorbents have been proposed, consisting of a ligand that can specifically interact with the metal ions, and a carrier matrix that may be an inorganic material (e.g., silica) [14,15,17] or polymers (such as polyA C H T U N G T R E N N U N G (styrene), poly(methacrylate), or poly(vinylbutyral)).…”
Section: Introductionmentioning
confidence: 99%